Improvement of molecular tools for the model diatom Thalassiosira pseudonana - Annika Messemer; Per Winge; Tore Brembu (Algal Research, 2026)

Principles and Methods of Counteracting Harmful Salmon–Arthropod Interactions in Salmon Farming: Addressing Possibilities, Limitations, and Future Options - Prashanna Guragain; Max Tkachov; Anna Solvang Båtnes; Yngvar Olsen; Per Winge; Atle M. Bones (Frontiers in Marine Science, 2021)
The arthropod salmon louse ( Lepeophtheirus salmonis ) is a major threat to Atlantic salmon aquaculture and wild salmonids. Essentially like in monoculture, very high concentrations of susceptible hosts may result in high reproduction and severe production of waves of pests. Pest management is crucial both for fish health and protection of wild fish populations from aquaculture influence. Various methods have been utilized to control salmon lice infestations, such as pesticide use, physical treatments, construction modifications, fallowing, breeding, vaccination, and biological control. Most of the methods are partially successful, but none completely fulfills the necessary pest control strategy. Like in agriculture, lice/pest management is an arms race, but the marine environment makes it even more difficult to precisely hit the target pest and avoid unintended negative effects on general wildlife. In this study, we provide an overview of the methods and principles of salmon lice management and address current possibilities and limitations. We also highlight the potential of emerging strategies and enabling technologies, like genome editing, RNA interference, and machine learning, in arthropod management in aquaculture.

Phenylalanine Hydroxylase RNAi Knockdown Negatively Affects Larval Development, Molting and Swimming Performance of Salmon Lice - Prashanna Guragain; Bjørnar Sporsheim; Astrid Skjesol; Anna Solvang Båtnes; Yngvar Olsen; Atle M. Bones; Per Winge (Frontiers in Marine Science, 2020)
Phenylalanine hydroxylase (PAH) is a crucial enzyme involved in tyrosine biosynthesis, having roles in neurological and physiological processes. The purpose of PAH has received little attention in crustaceans despite extensive investigations in other arthropods. Here, we characterize the PAH gene for the first time in the parasite Lepeophtheirus salmonis , a copepod that is responsible for huge economic losses in salmonid fish farming. Phylogenetic and sequence analyses confirmed that LsPAH is closely related to the metazoan PAH with conserved ACT regulatory and catalytic domains. Temporal expression patterns revealed that LsPAH is expressed throughout all developmental stages peaking during the copepodite stages, suggesting an essential role in developmental physiology. We used RNAi to knockdown LsPAH expression in the nauplius I stage to study developmental function during the larval stages. PAH knockdown impaired larval development, molting and swimming ability with severe morphological defects. This study provides insight into the role of PAH in copepods and demonstrates the importance of this metabolic gene in salmon louse growth and development.

Light Regulation of LHCX Genes in the Benthic Diatom Seminavis robusta - Lander Blommaert; Emmelien Vancaester; Marie J. J. Huysman; Cristina M. Osuna-Cruz; Sofie D’hondt; Johann Lavaud; Bernard Lepetit; Per Winge; Atle M. Bones; Klaas Vandepoele; Wim Vyverman; Koen Sabbe (Frontiers in Marine Science, 2020)

Genome editing in diatoms: achievements and goals - Peter G. Kroth; Atle M. Bones; Fayza Daboussi; Maria I. Ferrante; Marianne Jaubert; Misha Kolot; Marianne Nymark; Carolina Río Bártulos; Andrés Ritter; Monia T. Russo; Manuel Serif; Per Winge; et al. (Plant Cell Reports, 2018)

Genome-wide gene expression profiles in response to plastid division perturbations - Jodi Maple; Per Winge; Astrid Elisabeth Tveitaskog; Daniela Gargano; Atle M. Bones; Simon Geir Møller (Planta, 2011)

Catching the WAVEs of Plant Actin Regulation - Tore Brembu; Per Winge; Atle M. Bones (Journal of Plant Growth Regulation, 2005)

Cloning and characterization of rac-like cDNAs from Arabidopsis thaliana - Per Winge; Tore Brembu; Atle M. Bones* (Plant Molecular Biology, 1997)